2020
DOI: 10.1186/s13570-020-0158-4
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral community practices, microbial quality and associated health risks of raw milk in the milk value chain of Nakasongola District, Uganda

Abstract: The informal milk value chain in Uganda controls most of the raw marketed milk, albeit of poor quality. A study was conducted to assess the milk handling practices, the bacterial quality and the associated health concerns of raw milk along the informal milk value in Nakasongola District. The cross-sectional study used both qualitative and quantitative methods to obtain information from key players. The qualitative data was categorized and presented into emerging themes. Bacterial contamination of 200 milk samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
7
13
1
1
Order By: Relevance
“…Overall, our study showed a high proportion of resistance (71.5%) to at least one antibiotic tested, with no differences between S. aureus (75%) and CoNS (68%). This was slightly lower than reported in other studies in Malaysia (96.15%) and South Africa (90%) in S. aureus and CoNS, respectively [31,32] In contrast, a slightly lower resistance proportion in S. aureus (50%) and CoNS (50%) were reported in Uganda [33]. High resistance levels observed in this study could be linked to indiscriminate use of antimicrobials for treatment of mastitis in dairy cows by farmers and veterinarians [34].…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Overall, our study showed a high proportion of resistance (71.5%) to at least one antibiotic tested, with no differences between S. aureus (75%) and CoNS (68%). This was slightly lower than reported in other studies in Malaysia (96.15%) and South Africa (90%) in S. aureus and CoNS, respectively [31,32] In contrast, a slightly lower resistance proportion in S. aureus (50%) and CoNS (50%) were reported in Uganda [33]. High resistance levels observed in this study could be linked to indiscriminate use of antimicrobials for treatment of mastitis in dairy cows by farmers and veterinarians [34].…”
Section: Discussioncontrasting
confidence: 71%
“…Low resistance levels to quinolones and chloramphenicol were reported in this study among the staphylococci. Authors in Ethiopia [44], South Africa [32], Canada [7] and Uganda [33] reported similar findings. These critically important human-medicine antibiotics are restricted for use in treatment of animal diseases in many countries, including Kenya [32].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Milk contains a natural inhibitory system or temporary germicidal or bacteriostatic properties which prevents a significant rise in the bacteria count during the first 2 -3 hours (35,36) if cooled to temperature of 4ºC within this period immediately after milking that helps maintain its quality and safety for consumption (9,36). Our study found all the dairy farms to be storing milk at room temperature which is similar to finding of the studies done by Majalija et al(2020) (37) and Neeta et al(2014) (11). Water was found to be the most common adulterant added to milk in our study, similar to study in Kenya (37) and Belgaum (11) while the study in Chandigarh( 16)showed 85.4% not practising milk adulteration.…”
Section: Discussionsupporting
confidence: 91%